Komunikasi Persuasif Menggunakan Teknik Suggestive Selling dalam Transaksi Penjualan Terhadap Tingkat Penjualan pada Outlet Restaurant Pizza Hut Solo Square - Kartikawati, Sofiana; Hindra Hastuti, Nurnawati; Astuti Itasari, Andri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Starting from the phenomenon of declining sales that occurred at the Pizza Hut Solo Squarerestaurant outlet, this research was conducted to find out how the persuasive communicationprocess uses suggestive selling techniques in sales transactions on the level of sales at the PizzaHut Solo Square restaurant outlet, using descriptive qualitative methods, and using techniquescollection of observational data and in-depth interviews. This research was created in order toprovide insightful information to readers about the persuasive communication process usingsuggestive selling techniques used by cashier staff to consumers of Pizza Hut Solo Square. Theresults of the research carried out show that the persuasive communication process usingsuggestive selling techniques carried out in sales transactions by cashier staff to consumers,namely with a friendly attitude, using sentences that do not seem pushy and giving attentionand being a listener to consumers makes consumers feel comfortable and confident in makingtransactions, so that the cashier staff can recommend additional products that are useful forconsumers, in the form of selling combo packages (upselling) and selling complementary menus(cross selling). This suggestive selling not only benefits consumers but also the Pizza Hut SoloSquare restaurant outlet. Based on the results of this research, the process carried out by PizzaHut Solo Square staff in influencing consumers using persuasive communication withsuggestive selling techniques has a maximum impact on the sales level of the Pizza Hut SoloSquare outlet.Keywords: Persuasive Communication, Suggestive Selling